2006
DOI: 10.1007/s00421-006-0169-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of acute exercise on serum adiponectin and resistin levels and their relation to insulin sensitivity in overweight males

Abstract: The purpose of this study was to investigate the effects of a submaximal aerobic exercise bout on adiponectin and resistin levels as well as insulin sensitivity, until 48 h post-exercise in healthy overweight males. Nine subjects performed an exercise bout at an intensity corresponding to approximately 65% of their maximal oxygen consumption for 45 min. Adiponectin, resistin, cortisol, insulin, glucose and insulin sensitivity were measured prior to exercise, immediately after exercise as well as 24 and 48 h af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
2
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 28 publications
7
69
2
5
Order By: Relevance
“…In their investigation, nine obese males were subjected to one session of aerobic exercise for 45 minutes at approximately 65% of maximal oxygen uptake. They observed that insulin resistance index dropped and insulin concentration decreased immediately after the activity (27). In agreement with our findings, Rodnick et al reported that an aerobic exercise at 60% -70% of VO 2max for 30 -60 minutes had no effect on glucose tolerance test in subjects with type 2 insulin-resistant diabetic (28).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In their investigation, nine obese males were subjected to one session of aerobic exercise for 45 minutes at approximately 65% of maximal oxygen uptake. They observed that insulin resistance index dropped and insulin concentration decreased immediately after the activity (27). In agreement with our findings, Rodnick et al reported that an aerobic exercise at 60% -70% of VO 2max for 30 -60 minutes had no effect on glucose tolerance test in subjects with type 2 insulin-resistant diabetic (28).…”
Section: Discussionsupporting
confidence: 92%
“…The importance of this issue is due to the role of OXA in maintaining the hypothalamic sensitivity of insulin (26).Our results also showed an insignificant reduction in insulin levels and insulin resistance. These findings are inconsistent with the results of Jamurtas et al (27). In their investigation, nine obese males were subjected to one session of aerobic exercise for 45 minutes at approximately 65% of maximal oxygen uptake.…”
Section: Discussioncontrasting
confidence: 72%
“…In most studies, one single exercise could not show acute influence on the plasma adiponectin level, no matter the duration of exercise or whether the subjects are healthy or obese [84,[86][87][88][89]. However, an article published in 2010 reported that both high and low intensity anaerobic exercise could elevate blood adiponectin level in obese men [90], which is similar to the result of another report in 2006 using healthy men with anaerobic exercise [91].…”
Section: Adiponectin In Exercisementioning
confidence: 60%
“…56 Regardless of the type of physical activity, adiponectin levels did not change up to 48 h post a single submaximal cycling exercise session. 57,58 A 24-week endurance training program too had limited effect. 59 However, adiponectin resistance did improve following a 4-month resistance and endurance exercise program, independent of the change in body composition.…”
Section: Gender Age Mets and Adiponectinmentioning
confidence: 99%